2020
DOI: 10.1186/s13613-020-00653-z
|View full text |Cite
|
Sign up to set email alerts
|

The experience of high-flow nasal cannula in hospitalized patients with 2019 novel coronavirus-infected pneumonia in two hospitals of Chongqing, China

Abstract: Background: The outbreak of a novel coronavirus (2019-nCoV)-infected pneumonia (NCIP) is currently ongoing in China. Most of the critically ill patients received high-flow nasal cannula (HFNC) oxygen therapy. However, the experience of HFNC in this population is lacking. Methods:We retrospectively screened 318 confirmed patients with NCIP in two hospitals of Chongqing, China, from January 1st to March 4th, 2020. Among them, 27 (8.4%) patients experienced severe acute respiratory failure including 17 patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
244
0
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(271 citation statements)
references
References 19 publications
14
244
0
13
Order By: Relevance
“…Success rate of HFNC seems to be mostly dependent on the severity of pulmonary infection, with lower PaO2/FiO2 ratios resulting in a higher chances of therapy failure. Wang et al [9] described failure of HFNC in 63% when PaO2/FiO2 was below 200 mmHg, comparable with our group. Previous studies have shown that vulnerability is associated with worse clinical outcomes including mortality and duration of hospitalization in non-COVID patients [18,19].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Success rate of HFNC seems to be mostly dependent on the severity of pulmonary infection, with lower PaO2/FiO2 ratios resulting in a higher chances of therapy failure. Wang et al [9] described failure of HFNC in 63% when PaO2/FiO2 was below 200 mmHg, comparable with our group. Previous studies have shown that vulnerability is associated with worse clinical outcomes including mortality and duration of hospitalization in non-COVID patients [18,19].…”
Section: Discussionsupporting
confidence: 91%
“…We found an overall case rate survival much lower than most reported survival rates on the clinical wards [6,16,17].However, our cohort is a selection of frail patients with severe respiratory failure and high ARDS scores. Recently two other studies were published describing the successful use of HFNC in COVID-19 patients [8,9]. Contrary to these studies, we did not use HFNC therapy as an intermediate step-up between invasive mechanical ventilation and conventional oxygen therapy.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…2 This system has demonstrated utility in the management of patients with respiratory distress and COVID-19, with guidelines recommending its use as the firstline strategy for patients with acute hypoxemic respiratory failure, despite conventional oxygen therapy. 1,2,5 Even though high-flow nasal cannula provides flow rates at 40-60 liters per minute, a cough has flow rates approaching 400 liters per minute, and evidence suggests that high-flow nasal cannula is not associated with high risk of viral transmission when appropriately connected. 6,7 If used, the FiO2 should be set at 100% with an initial flow rate set to 20 liters per minute.…”
Section: What Is High Flow Nasal Cannula and How Should It Be Started?mentioning
confidence: 99%